Applying attribute grammars to teach linguistic rules - Barros, Patrícia Amorim (2017)
An attribute grammar is a very well known formalism to describe computer languages but it can also be successfully used to describe linguistic phenomena. Since natural languages can also be expressed in grammars it is natural to describe rules using the same formalism. Linguistic teachers of the University Complutense of Madrid started using attribute grammars but they lack a tool that helps them to specify linguistic rules in a friendly and natural way. Therefore we propose a domain specific language (NLSdsl) carefully designed for non-programmers that will be implemented on an AnTLR based system.